14
$\begingroup$

Problem. Let $f\in C^1(\mathbb R)$ such that $f(0) = 0$ and $0 < f'(x) \le 1$. Prove that for all $x\ge 0$ $$ \int_0^x f^3(t)\,dt \le \left(\int_0^x f(t)\,dt\right)^{\!\!2}. $$

Below is my solution of this simple problem, but I want to see alternative proof (just for fun). Thank you for your time!

Since $f'(x) > 0$ then $f(x) > 0$ while $x>0$. $f'(x)\le 1$ is given; let's multiply it by $2f(x)$: $$ 2f(x)f'(x) \le 2f(x). $$ Let's integrate this inequality from $0$ to $x$: $$ \int_0^x 2f(t)f'(t)\,dt \le \int_0^x 2f(t)\,dt, $$ but $$ \int_0^x 2f(t)f'(t)\,dt = \int_0^x \frac{d}{dt} \Big(f^2(t)\Big)dt = f^2(x) - f^2(0) = f^2(x). $$ So, $$ f^2(x) \le 2\int_0^x f(t)\,dt $$ Let's multiply it by $f(x) > 0$: $$ f^3(x) \le 2f(x)\int_0^x f(t)\,dt, $$ and integrate: $$ \int_0^x f^3(t)\,dt \le \int_0^x 2f(t)\left(\int_0^t f(u)\,du\right)dt $$ Denote $F(t) = \displaystyle\int_0^t f(u)\,du$. Then RHS is $$ \int_0^x 2f(t)F(t)\,dt = \int_0^x 2F'(t)F(t)\,dt = \int_0^x \frac{d}{dt} \Big(F^2(t)\Big)dt = F^2(x) - F^2(0) = F^2(x), $$ or $$ \int_0^x f^3(t)\,dt \le \left(\int_0^x f(t)\,dt\right)^2. $$

EDIT

Solution of @J. J. is pretty and correct, but it's not so alternative. In other words, we prove that $f(x)-g(x)\ge 0$ instead of $f(x)\ge g(x)$. I want to see proof with known integral inequalities (like Cauchy-Schwarz, for example).

$\endgroup$

1 Answer 1

16
$\begingroup$

Let $$h(x) = \left(\int_0^x f(t) \, dt\right)^2 - \int_0^x f^3(t) \, dt.$$ We need to show that $h(x) \ge 0$ for $x \ge 0$. Clearly $h(0) = 0$ so it is enough to show that $h'(x) \ge 0$ for all $x \ge 0$. We have $$h'(x) = 2 \int_0^x f(t) \, dt f(x) - f^3(x) = f(x) \left( 2 \int_0^x f(t) \, dt - f^2(x) \right),$$ so it is enough to show that $g(x) := 2 \int_0^x f(t) \, dt - f^2(x) \ge 0$ for all $x \ge 0$. Now clearly $g(0) = 0$ so it is enough to show that $g'(x) \ge 0$ for all $x \ge 0$. We have $$g'(x) = 2 f(x) - 2 f(x) f'(x) = 2f(x)(1 - f'(x)) \ge 0,$$ which proves the claim.

$\endgroup$
3
  • $\begingroup$ I didn't look at the original proof too closely, but in hindsight I suspect this is pretty much the same. I perform two differentiations and the original seems to start the other way around and does two integrations. $\endgroup$
    – J. J.
    Aug 5, 2015 at 14:00
  • $\begingroup$ Yes, it's almost the same. By the way, it's more clearer and strightforward (for me). Thanks. $\endgroup$ Aug 5, 2015 at 14:16
  • 1
    $\begingroup$ I'm amazed by the usefulness of the trivial fact that you've used: To show that the function is positive for positive values, it's enough to check that its value at zero is positive and that its derivative is positive. $\endgroup$
    – Mihail
    Aug 5, 2015 at 16:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.